Tradizione e Innovazione nel Restauro Archeologico - Crova, Cesare (Archeomatica, 2023)
As part of the conservation projects that have affected the Villa dei Quintili, an important role has been played by the educational sites which over the last 11 years have seen alternating, in an interdisciplinary work between the Archaeological Superintendence of Rome and the Archaeological Park of 'Appia Antica' with the School of Specialization in Architectural and Landscape Heritage of the "Sapienza" - University of Rome and, above all, the Central Institute for Restoration. In particular, over the years the ICR has played the role of consultant for academic activities and, subsequently, of main actor in the conservation sites of a portion of the central area and the area of the Carceres, with particular reference to the conservation of opus sectile that are found here, the starting point for experiences that will be developed in the near future.